For Them but Never Really Theirs: Finding a Place for the “Aged” Within State-Funded Institutions in Nineteenth-Century Nova Scotia - DesRoches, Cheryl (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2009)
AbstractThis paper reveals that between 1867 and the 1890s, care for the aged within state funded institutions in Nova Scotia underwent several important changes that reflected the intentions of the province to avoid long term responsibility for the needy. It argues that throughout this period government officials championed institutionalization as a fiscally responsible solution to the rising number of those in need, including the sick, poor and mentally insane; as a result, state funded homes for the aged developed by default rather than by design. Following confederation, the persistence of poor laws and weak local governments ensured the townships’ continued reliance on the province for support of their needy. By the end of the 1870s, it became apparent that the old system of social welfare in Nova Scotia was in need of decisive change and a two-tier system — municipal and provincial institutions for the harmless insane and the less-fortunate — came to be seen as the solution. The creation of a two-tier system in the late 1880s afforded greater opportunities for the province to disentangle some of its social welfare services by offering specialized services to specific groups — hospitals for the sick and the insane and poorhouses for the indigent (including the aged) at both the provincial and municipal levels. In the 1890s, many counties utilized what had long been a provincial model for institutional care and focused primarily on the largest portion of the inmate populations that could work: the harmless insane. Increasingly, they built institutions that allowed them to maximize inmate labour to dissipate costs. However, as municipalities built or improved asylums for the harmless insane, non-workers such as the aged were left behind in dilapidated poor farms. By the turn of the century, as the aged were identified as a unique group, these run down facilities became the earliest state-funded nursing homes for the indigent aged in Nova Scotia.